Chega de Fiu Fiu - Frazão, Fernanda; Kamanchek, Amanda (Brazil, 2018)
Were the cities made for women? The film tells the story of Raquel, Rosa and Teresa, who live in three different Brazilian cities and, through activism, art and poetry, resist and propose new ways of living in the public space.
Verzio Film Festival Submission
Keywords: Documentary films